スニチニブ投与患者に発症した顎骨壊死の1例 - 岩田, 英治; 岸本, 恵実; 古森, 孝英; 明石, 昌也; 古土井, 春吾; 鰐渕, 聡 (日本口腔外科学会雑誌, 2018)
Osteonecrosis of the jaw is one of the problematic side effects observed during administration of angiogenesis inhibitors in patients receiving treatment for cancer. We report a case of osteonecrosis of the jaw in a patient receiving sunitinib.　The patient was a 72-year-old man who was referred to our hospital because of exposed bone and contact pain of the tongue. After the clinical diagnosis of osteonecrosis of the jaw, observation and irrigation of the exposed bone were frequently performed. Four months later, the lesion healed. After 1 year, exposed bone was found in other sites ; however, it disappeared a month later.　The present case suggests that the use of sunitinib can be associated with osteonecrosis of the jaw and indicates that invasive dental treatment and the status of the main disease should be considered when prescribing sunitinib, as is done when prescribing bisphosphonates or denosumab.